Thermomechanical analysis of African tannins resins and biocomposite characterization. Issue 14 (18th July 2021) - Konai, Noel; Pizzi, Antonio; Danwe, Raidandi; Lucien, Meva'a; Lionel, Karga Tapsia
Abstract: The Daniellia oliveri, Ficus sycomorus, Butyrospermum parkii and Azadirachta indica barks tannins were extracted, used in the development of four different resins hardened with the Vachellia nilotica exudates and in the development of an unidirectional biocomposite reinforced with woven banana stalk fibers. The percentage yield of these tannins was, respectively, 29%, 46%, 40% and 35%. Their behavior and reactivity were studied using gel time and thermomechanical analysis. The F. sycomorus resin reacted well with V. nilotica as biohardener, its gel time was 600 s. The modulus of elasticity (MOE) of R1, R2, R3 and R4 resins formulations were, respectively, 2.37*10 3  MPa, 7.05*10 3  MPa, 4.62*10 3  MPa and 2.65*10 3  MPa. They degraded, respectively, at 183, 174, 139 and 165 °C. The MOE and bending strength (MOR) of each unidirectional biocomposite were, respectively, 10; 24; 18; 15 GPa and 52; 78; 66; 60 Mpa.